Strategi Remarketing Dan E-Payment Untuk Meningkatkan Volume Penjualan Pada E-Commerce - Ika Novaliana (Edumedia Solution, 2023)
The remarketing strategy of utilizing electronic technology (e-commerce) as a buying and selling medium that uses the internet to promote its products by utilizing e-payment information technology will make it easier for customers to make non-cash payment transactions so that they are practical and efficient. This study aims to analyze remarketing and e-payment strategies in an effort to increase sales volume on e-commerce sites. This study uses a quantitative approach with a causal associative method. The data collection technique uses a questionnaire given to respondents using the Google Forms platform. The population and sample in this study were 97 STIE Nganjuk students, namely students who had shopped online on e-commerce sites using e-payment. For sampling, using purposive sampling technique, with multiple linear regression analysis technique. Hypothesis testing through t test (partial) and F test (simultaneous). The results showed that remarketing had a partial and significant effect on sales volume, as evidenced by the acquisition of a t count value greater than t table with a significance of less than 0.05. E-Payment has a partial and significant effect on sales volume, as evidenced by the acquisition of a t count value that is greater than t table with a significance of less than 0.05.